An Exposition of the New Strategy, 'Promoting Peace and Stability in the Middle East and North Africa' - Devarajan, Shantayanan (World Bank, Washington, DC, 2016)
The Middle East and North Africa region is in turmoil. Syria, Iraq, Libya and Yemen are in civil war, causing untold damage to human lives and physical infrastructure. Fifteen million people have fled their homes, many to fragile or economically strapped countries such as Jordan, Lebanon, Djibouti and Tunisia, giving rise to the biggest refugee crisis since World War II. Palestinians are reeling from deadly attacks and blockades. With recruits from all over the world, radicalized terrorist groups and sectarian factions like Daesh are spreading violence around the globe, threatening some governments' ability to perform basic functions. Countries undergoing political transitions, such as Egypt, Tunisia, Morocco and Jordan, face periodic attacks and political unrest, leading them to address security concerns over inclusive growth. Even relatively peaceful oil exporters, such as Algeria, Iran and the GCC, are grappling with youth unemployment and poor-quality public services, the same problems that contributed to the Arab Spring, alongside low oil prices. Finally, the author will develop and monitor input indicators that are consistent with the theory of change associated with the new strategy. We will have indicators that show whether our interventions are helping to renew the social contract (the use of citizen engagement in projects is an example). Household surveys can tell us whether the welfare of refugees and host communities is improving. Preparedness indicators can be used to inform progress on the recovery and reconstruction pillar. And standard indicators such as the share of electricity production that is traded will be used for the regional integration pillar.